Like water on stone - Walrath, Dana (Delacorte Press, 2014)
Based on actual events, this novel in verse relates the tale of siblings Sosi, Shahen, and Mariam who survive the Armenian genocide of 1915 by escaping from Turkey alone over the mountains.